An examination of the relationship between flexible work arrangements, work-family conflict, organizational commitment, and job performance = Badanie związku między elastycznymi ustaleniami dotyczącymi pracy, konfliktem między rodziną a pracą, zaangażowaniem organizacyjnym i wydajnością pracy - Ongaki, Jacob (Zielona Góra: Faculty of Economics and Management Press)
Many employees are often faced with an inter-role conflict between work and that of a family in the U.S. However, business leaders and Human Resource Management (HRM) may not recognize the problem affecting white-collar employees. The purpose of this non-experimental quantitative study was to determine whether or not a relationship existed between employees' use of flexible working arrangements as predictor variables (such as flexible work schedules and telecommuting) and work-family conflict and family-work conflict as covariate variables, and organizational outcomes (such as organizational commitment and job performance outcome variables).
Keywords: elastyczne warunki pracy; elastyczne harmonogramy pracy; wydajność pracy; zaangażowanie organizacyjne; telepraca; konflikt praca-rodzina; flexible work arrangements; flexible work schedules; job performance; organizational commitment; telecommute; work-family conflict